Analysis of Lifestyle, Social Class and Brand Reputation on Purchase Decisions - Astana, I Gusti Made Oka; Hidayat, Ujang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aimed to examine the influence of lifestyle, social class, and brand reputation on curtain purchase decisions at Toko Ayu Gorden Singaraja. This study is quantitative in nature. This study's population comprises individuals who have made purchases from Toko Ayu Curtains Singaraja. As the sampling technique for this research is Probability Sampling and the sampling method is Simple Random Sampling, the sample in this study consists of forty respondents. Classical assumption testing, multiple linear regression analysis, the t-test, and the f-test are used for analysis. Lifestyle influences the decision to purchase draperies at Toko Ayu draperies Singaraja, according to the results. The results indicated that the t-test for hypothesis testing yielded a t-count greater than the t-table. The results of the lifestyle, social class, and brand reputation analyses have a significant impact on curtain purchases at the ayu curtain shop. The calculated F value is 22,292, which indicates that it is greater than the F table. The hypothesis H1 is therefore accepted in this investigation. Consequently, it can be concluded that lifestyle, social class, and brand reputation have a substantial impact.